THE CONVERSATIONAL IMPLICATURE IN THE SERIES OF AL-ZEER SALEM (ABU LAILA AL-MUHALHAL) AS A PRAGMATIC APPROACH TO THE SPEECH OF REVENGE FOR KULAIB'S BLOOD - Adnan Rasmi Yasir; Sadeq Omair Jalood (Scholar Express Journal, 2022)
The research revolves around the conversational Implicature as one of the deliberative arguments advocated by (Grace) in his research. It is based on the core idea that people in their conversations mean more than they say. Based on this, the imperative is the indirect or implicit speech that the speaker hides from his hearer. This paper dealt with the discourse of revenge as an annihilating discourse. The blood seeker (the Zeer) was intentionally - in my opinion - to use indirect speech with his enemies until he puts them in a circle of confusion and the question is what does he want? Why did he want this and not others....etc.
Keywords: Conversational Implicature; Grace; Al-Zeer Salem Series; Revenge